Implementation of KOHA Integrated Library Management System in Wollega University Main Library, Nekemte, Ethiopia: A Study - Kantappa, Niranjana; Desta, Tolessa; Paul, M.; Vijaya Kumar, N. (Journal of Information and Knowledge, 2020)
KOHA is widely used library automation software in the world with provisions for all library operations. This paper examines the implementation of Koha in Wollega University Library the challenges faced in the implementation of Koha and provides solutions to some of the challenges faced. This paper aims to elaborate the method of installation of KohaKoha, steps for data migration from Excel to KOHA and upgrading process of KOHA version from 17.05 to 19.05.05. This is a case study conducted at Wollega University, Nekemte. The paper identifies several issues concerning data migration within a local scenario and elaborates how Koha software installed and customised for university needs. The lesson learnt and the experience gained would help in similar exercises elsewhere.